EFEK TRAUMATIS PADA KELOMPOK DEWASA PASCA TERJADINYA BENCANA: META ANALISIS - Dwi Handayani; Bertha M Sopha; Budi Hartono; M K Herliansyah; Avin F Helmi (Teknoin, 2015)
Various studies in the field of traumatic effect or stress after disaster, commonly known as PSTD or Post-Traumatic Stress Disorder have been caried out. Many researchers have tested the effects of disasters and PTSD, but the correlation value are different. The purpose of this study was to obtain the actual value of the correlation. This study collected the correlation value of 21 existing research results. The results of this study showed that the average of correlation is 2SD greater than 0 equal to 0.069864. This value has been indicated that there is positive correlation between disaster and Stress (PTSD), so the hypothesis is accepted by the population correlation value 0.074256, sampling error 0.43%. It shows that disaster variable always positively correlated to increased stress behavior among adults.